A preliminary investigation of childhood anxiety/depressive symptomatology and working memory across multiple units of analysis. (April 2021) - Kavanaugh, Brian C.; Fryc, Alexa; Temereanca, Simona; Tirrell, Eric; Oberman, Lindsay; Carpenter, Linda L.; Spirito, Anthony
Highlights: Frontal theta-gamma coupling (TGC) was correlated with working memory performance TGC, test performance, and symptoms were combined to create a composite score This multi-level composite predicted self-reported anxiety/depressive symptoms Frontal TGC was the only level that independently predicted symptoms Abstract: This exploratory study examined multiple units of working memory (WM) analysis in a transdiagnostic, treatment-seeking, pediatric sample. This included a) an electroencephalography marker of WM (coupling of theta and gamma oscillations [i.e., theta-gamma coupling] in frontal brain regions), b) WM test performance, and c) parent-reported WM symptoms. A composite score combining each of these units of analysis correlated with self-reported depressive and anxiety symptoms, with only theta-gamma coupling independently predicted anxiety/depressive symptoms. Results confirm prior findings on the association between WM and anxiety/depression, although the majority of this variance was explained by frontal theta-gamma coupling during WM demands.